An Alternative Reading of Amor Towles’s A Gentleman in Moscow - Acharya, Rajendra (Interdisciplinary Journal of Management and Social Sciences, 2021)
This paper explores Amor Towles’s A Gentleman in Moscow (2016) as an Alternative Reading of Stalinian Era in terms of its reinterpretation of the Russian history and scrutinization of the historical documents. In doing so, this paper endeavors to study Amor Towles’s A Gentleman in Moscow (2016), through the vantage point of Foucauldian discourse supported by Friedrich Nietzsche’s notion of ‘freewill’, Catherine Gallaher and Stephen Greenblatt’s notion of ‘counter history. This Article further delves in to the official history and examines the power-politics of and behind the critique of Stalinian regime by observing the socio-cultural background of the author. The paper also offers more than one potential reading of Russian history and the novelist’s social context in order to analyze the novel as a direct outcome of the clashing interpretations and concludes that, Towles, while crafting historical fiction, explicitly tantalizes Russian history, implicitly emphasizes American values and creates the new knowledge for the sake of subjugated through artistic discourse. Finally, the paper will demonstrate that the novelist invites the reader to concentrate and support the political power of marginalized group despite its absence in official history.